In the matter of colorful painting: from Hegel, Goethe and Diderot - Werle, Marco Aurélio; Restrepo, Carlos Enrique (Estudios de Filosofía, 2012)
The consideration of Colouring presented by Hegel to establish a superior category of it over Drawing or Sketching is based in the fact that the latter two are not substantial in Pictorial Representation. Hegel establishes a point of turn in respect to ideas about the supremacy of Form over Colouring that were set forth by authors such as Immanuel Kant or Johan J. Winckelmann. Hegel approaches the Conceptions of Color of Goethe and Diderot to be able to grasp the subjective character of these, where Color is given in the Realm of Human Perception independently of any other Objective Theory, but at the same time it remains reluctant to Universal Laws of Harmony that are the basis of the Goethian Theory which works only for Natural Philosophy but not for Artistic Philosophy such as it is reflected in the Theory of Diderot and in Flemish painting.